Diffusion‐driven continuous‐wave‐pumped organic dye lasers. Issue 5 (28th July 2015) - Coles, David M.; Trichet, Aurélien A. P.; Dolan, Philip R.; Taylor, Robert A.; Vallance, Claire; Smith, Jason M.
<x xml:space="preserve">Abstract</x> An organic dye laser with ultra‐small mode volume of approximately 11 cubic microns is demonstrated. The self‐diffusion of the dye molecules within the cavity replenishes the gain medium on a timescale concomitant with the photobleaching time of the dye, allowing for operation in the continuous wave pumping regime for 10's of seconds. These compact lasers could find application in lab‐on‐a‐chip spectroscopy systems.